2007
DOI: 10.1080/00365590600991268
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of conservatively managed incidental carcinoma of the prostate A multivariate analysis of prognostic factors

Abstract: Elderly men with category T1a and/or Gleason score 4-5 prostate cancer have a favourable prognosis with conservative management. Immunohistochemical staining with Ki-67 may be of help in situations where further prognostic information is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
(14 reference statements)
0
28
0
5
Order By: Relevance
“…They reported that higher Gleason grade, higher nuclear grade, and larger tumour volume were independent predictors of death in prostate cancer. In another report, Robinson and colleagues 6 found that 33 (17%) of 197 cases of incidental prostate cancer who were managed conservatively died from prostate cancer during the mean 7.8-year follow-up. Again, their data indicated that high Gleason score, T1b, and high immunoreactivity of Ki-67 were independent predictors of diseasespecific mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that higher Gleason grade, higher nuclear grade, and larger tumour volume were independent predictors of death in prostate cancer. In another report, Robinson and colleagues 6 found that 33 (17%) of 197 cases of incidental prostate cancer who were managed conservatively died from prostate cancer during the mean 7.8-year follow-up. Again, their data indicated that high Gleason score, T1b, and high immunoreactivity of Ki-67 were independent predictors of diseasespecific mortality.…”
Section: Resultsmentioning
confidence: 99%
“…4 Although most of the incidental prostate cancers are considered clinically insignificant, recent studies have suggested that in some of them, the clinical course becomes more unfavourable. 5,6 The main preoperative diagnostic tools to confirm prostate cancer include serum concentration of prostate-specific antigen (PSA), digital rectal examination (DRE), and imaging modalities. The positive predictive values, however, of DRE 7 and transrectal ultrasonography (TRUS) 8 are limited.…”
Section: Introductionmentioning
confidence: 99%
“…For the T1a category without invasive therapy, Chodak et al [25] and Jonsson et al [4] reported tumour-specific survival of 94% after 10 years, and 90% after 15 years. Robinson et al [5] studied 197 patients with T1a/b disease who were on WW.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of IPCa has been reported to be 5.2-6.4% [2,3], but no unequivocal statement regarding the appropriate treatment has thus far been made, because only studies with small numbers of cases are currently available. For patients with IPCa and a low Gleason score (≤6) there are good reasons for proceeding with non-invasive protocols, as several studies have shown that cancer-specific survival times are approximately equal to normal life expectancy [4,5]. Noninvasive approaches include active surveillance (AS) and watchful waiting (WW).…”
Section: Introductionmentioning
confidence: 99%
“…The PSA levels were measured at three laboratories in the healthcare region and the laboratories were operating under standardised conditions (with a method calibrated against the Stanford 90:10 PSA standard [187]. A pathology re-review of Gleason scoring in this register was also performed and high immune reactivity of Ki-67 was suggested as independent adverse predictor of disease-specific mortality in patients after initial watchful waiting [188]. A further strength of the study is that the SERPCR has a high validity regarding cause of death based on comparison of registration in the SERPCR and that in the national Cause of Death Register.…”
Section: Paper Imentioning
confidence: 99%